2010
DOI: 10.1111/j.1537-2995.2010.02688.x
|View full text |Cite
|
Sign up to set email alerts
|

An update on platelet transfusion in hematooncology supportive care

Abstract: S everal key aspects of platelet (PLT) transfusion supportive care in cancer management remain uncertain. Included are both the optimal transfusion trigger and the optimal PLT dose required to limit bleeding-related morbidity and mortality from thrombocytopenia. This update provides a brief history of PLT transfusion and summarizes the knowledge about factors, including PLT count, that are associated with bleeding risk. International guidelines are available addressing prophylactic PLT transfusion thresholds i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 53 publications
0
12
0
3
Order By: Relevance
“…70,[72][73][74][75] Two additional prospective studies also demonstrated safety with the lower threshold of 10 ϫ 10 9 /l for prophylactic platelet transfusions. 76,77 The effect of these thresholds on numbers of platelet and blood transfusions is variable, however 77 ; one study demonstrated a 36% and 16% reduction in platelet and blood transfusions, respectively, 77 whereas another showed no differences. 76 A recent trial 78 demonstrated that "low-dose" prophylactic platelet transfusions are equally effective as those with "standard" or "high" dose.…”
Section: Indications For Platelet Transfusionmentioning
confidence: 99%
“…70,[72][73][74][75] Two additional prospective studies also demonstrated safety with the lower threshold of 10 ϫ 10 9 /l for prophylactic platelet transfusions. 76,77 The effect of these thresholds on numbers of platelet and blood transfusions is variable, however 77 ; one study demonstrated a 36% and 16% reduction in platelet and blood transfusions, respectively, 77 whereas another showed no differences. 76 A recent trial 78 demonstrated that "low-dose" prophylactic platelet transfusions are equally effective as those with "standard" or "high" dose.…”
Section: Indications For Platelet Transfusionmentioning
confidence: 99%
“…We determined evidence-based appropriateness criteria from a variety of sources [15][16][17][18][19][20][21][22][23]. The most recently published guidelines from the American Association of Blood Banks (AABB) are similar to our institutional criteria.…”
Section: A Priori a Priori Appropriateness Criteriamentioning
confidence: 99%
“…The majority of platelet (PLT) transfusions are given prophylactically to prevent bleeding in hematooncology patients with thrombocytopenia . Timing of these transfusions is based on PLT count triggers . PLT counts alone are known to correlate poorly with bleeding risk, suggesting that PLT function could be a potentially important additional variable to take into account.…”
mentioning
confidence: 99%